Dolphin mysteries : unlocking the secrets of communication - Dudzinski, Kathleen; Frohoff, Toni, 1963- (Yale University Press, 2008)
From the Publisher: Dolphins have fascinated humans for millennia, giving rise to an abundance of stories and myths about them, yet the actual details of their lives in the sea have remained elusive. In this enthralling book, Kathleen M. Dudzinski and Toni Frohoff take us into the dolphins' aquatic world to witness firsthand how they live their lives, communicate, and interact with one another and with other species, including people. Kathleen M. Dudzinski and Toni Frohoff are scientists who have collectively dedicated more than 40 years to studying dolphins beneath the ocean's surface, frequently through a close-up underwater lens. Drawing on their own experiences and on up-to-the-minute research, the authors show that dolphins are decidedly not just members of a group but distinct individuals, able to communicate with one another and with humans. Dudzinski and Frohoff introduce a new way of looking at, and listening to, the vocabulary of dolphins in the sea, and they even provide an introductory "dolphin dictionary," listing complex social signals that dolphins use to share information among themselves and with people. Unveiling an intimate and scientifically accurate portrait of dolphins, this book will appeal to everyone who has wanted a closer glimpse into the hearts and minds of these amazing creatures.